Chapter Monitoring coastal areas: a brief history of measuring instruments for solar radiation - De Vincenzi, Matteo (Proceedings e report, 2020)
The first measuring instruments of solar radiation, for meteorological aims, were made only in 1800s. In 1896 OMI established a commission for radiometry which led, in 1905, to choose Ångström pyrheliometer as standard instrument. Later, radiometers were built with a chart recorder for measuring solar radiation components. Instruments using thermopile or photocell as sensitive element were made. From 1980s radiometers with data logger were built. In 2000s devices were developed for measuring solar radiation components in water column, for studies on physical and biological marine quantities.